Transcription of DNA-histone complexes by yeast RNA polymerase B. - Karagyozov, L K (1978)
Transcription of denatured DNA complexed with histones (total, H1 or H2A/H2B/H3/H4) by yeast RNA polymerase B is investigated. Binding of histones to DNA restricts its template activity by decreasing the formation of active, heparin-resistant, RNA polymerase initiation complexes. The elongation of pre-initiated RNA on denatured DNA, complexed with histones, is possible, although resulting in somewhat shorter RNA chains. It is suggested that RNA polymerase B can elongate on a DNA strand covered with histones.